KONSEP PSIKOTERAPI KAWRUH JIWA KI AGENG SURYOMENTARAM - KHOLIK, ABDUL ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This research is purposed to find out how the process of kawruh jiwa with its ngudari reribet becomes a psychotherapy concept based on sensitivity. This research was using a qualitative approach with deepen phenomenology therminology. The respondents in this research were two students of kawruh jiwa. Data were obtained by interview method and literature data triangulation. The research result was finding that mawas diri by the process of kandha-takon through nyawang karep in order to nyocokaken raos in ngudari reribet as essence of kawruh jiwa of Ki Ageng Suryomentaram psychotherapy. The process of kandha-takon was covered kandha takon pasinaon raos with purposed to develop ngudari reribet technique. The character of this kandha-takon was luluh (sirnaning raos aku-kowe) and its correlation was egalitarian, which meant without having the feeling of being a teacher and a student. Other process of kandha-takon was kandha takon jawah kawruh with character of njujug raos (njujug raosipun tiyang sanes sejatine njujug raosipun piyambak). Mawas diri with nyawang karep in order to nyocokaken raos in ngudari reribet was covered kandha-takon interpersonal dimension, also known as problems sharing into the feeling of oneself perception and kandha-takon intrapersonal dimension, which took place by oneself known as nyawang karep with character of looking into oneself or introspective. This kandha-takon covered: first, mawas diri dynamic as the experience of looking into oneself by looking into the feeling of others within the feeling of oneself